(3YdGbGJ GdehQOjf (B"(3eONd GOGQj(B"s - (3Thbj fGLj(B, (3LhGOs; (3eMeO SGde(B, (3GdTehWs ((3YeGf(B:s (3GKQGA ddfTQ h GdJhRjY(B,s, 2008)
(3EOGQI SdSdI GdJhQjO(B''(3YdGbGJ GdJhQjO(B''- (3GdJRhO ef GdeUGOQ hGNJjGQ GdehQOjf(B- (3YdGbGJ GdehQOjf(B- (3efXeGJ GdJhQjO(B- (3JcfhdhLjG GdeYdheGJ hSdSdI GdJhQjO(B- (3JhQjO GdNOeGJ(B- (3JcGed SdSdI GdJhQjO(B- (3GdJhQjO GdYGdej(B- (3GdHMK hGdbjGS aj YedjGJ GdJhQjO(B- (3GdCNdGbjGJ hGdeSDhdjI GdELJeGYjI ddJhQjO(B- (3eSJbHd SdSdI GdJhQjOs
(3cTGa GdeUWdMGJ U(B.221(3; SjQI MjGI GdeDGajf U(B.233s
Keywords: (3EOGQI GdEfJGLs; (3EOGQI GdeTJQjGJs; (3GdJhQjOs; (3JcfhdhLjG GdeYdheGJs